Single-nucleotide resolution mapping of m6A and m6Am throughout the transcriptome - Linder, Bastian (Nat Methods, 2015)
N(6)-methyladenosine (m6A) is the most abundant modified base in eukaryotic mRNA and has been linked to diverse effects on mRNA fate. Current m6A mapping approaches localize m6A residues to 100–200 nt-long regions of transcripts. The precise position of m6A in mRNAs cannot be identified on a transcriptome-wide level because there are no chemical methods to distinguish between m6A and adenosine. Here we show that anti-m6A antibodies can induce specific mutational signatures at m6A residues after ultraviolet light-induced antibody-RNA crosslinking and reverse transcription. We find these antibodies similarly induce mutational signatures at N(6),2′-O-dimethyladenosine (m6Am), a nucleotide found at the first encoded position of certain mRNAs. Using these mutational signatures, we map m6A and m6Am at single-nucleotide resolution in human and mouse mRNA and identify snoRNAs as a novel class of m6A-containing ncRNAs.